Hybrid monitoring and measurement of concrete shielding activation at the ProtherWal proton therapy centre - Ramoisiaux, E.; Hernalsteens, C.; Tesse, R.; Gnacadja, E.; Pauly, N.; Stichelbaut, F. (EPJ techniques and instrumentation, 2023)
Proton therapy systems produce large fluxes of energetic secondary particles when tailoring the beam energy and transverse profile to the specificities of each irradiation plan. A Low Activation Concrete (LAC) mix is foreseen for parts of the shielding of the Ion Beam Applications (IBA) Proteus® One (P1) compact system at the ProtherWal proton therapy centre in Charleroi, Belgium, to limit the long-term activation of the concrete shielding. To experimentally monitor the long-term activation and validate the beneficial impact of the LAC mix, a setup of four removable cores to be placed at critical locations in the cyclotron vault is optimised. We report on the experimental and simulation monitoring setup design. Our validated BDSIM/FISPACT-II methodology combines particle tracking and Monte-Carlo particle-matter interactions simulations using Beam Delivery Simulation (BDSIM) and the computation of the activation using FISPACT-II. We show that the evaluation of the short-term activation of the cores is essential to the measurement analysis. We detail a hybrid workflow based on numerical simulations that uses logging data of the workloads of the clinical and research beam production and experimental measurements to evaluate and monitor the short- and long-term activation at any point during the centre lifetime and decommissioning period. The activation of the cores using a realistic foreseen irradiation pattern is studied, allowing for the characterisation of the measurement process and radiation protection considerations related to the measurement campaign. The final experimental setup and the supporting online simulation tools are discussed in detail.